(untitled) (Journal of Global Humanities and Social Sciences, 2024)
The flipped classroom, as an innovative teaching mode, has been widely used in applied universities, aiming to promote the improvement of students’ independent learning ability. By analyzing the implementation status quo of the flipped classroom in applied universities, this paper explores the influence of teachers’ roles, students’ factors, and instructional design on students’ independent learning ability, and based on this, proposes four strategies, including strengthening teachers’ training and development, optimizing the instructional design and content arrangement, stimulating students’ learning motivation and engagement, and establishing an effective feedback and support system. These strategies can effectively improve students’ independent learning ability, enhance their learning motivation, promote more efficient learning outcomes, and provide more accurate and effective teaching guidance for applied universities.